Activation of Mouse Cumulus-Oocyte Complex Maturation In Vitro Through EGF-Like Activity of Versican. Issue 5 (1st May 2015) - Dunning, Kylie R.; Watson, Laura N.; Zhang, Voueleng J.; Brown, Hannah M.; Kaczmarek, Adrian K.; Robker, Rebecca L.; Russell, Darryl L.
Abstract: In vitro maturation of oocytes is suboptimal to in vivo maturation with altered gene expression and compromised oocyte quality. The large proteoglycan versican is abundant in mouse cumulus-oocyte complexes (COCs) matured in vivo but is absent in cultured COCs. Versican is also positively correlated with human oocyte quality. Versican contains an epidermal growth factor (EGF) motif, and based on EGF-like activities in other systems we hypothesized that versican acts as an EGF-like signaling factor during COC maturation. Here, we purified recombinant versican and compared its function with that of EGF during in vitro maturation (IVM). Versican significantly increased cumulus expansion and induced cumulus-specific genes Ptgs2, Tnfaip6, and Has2, which was blocked by EGF receptor antagonist. Microarray analysis revealed that versican has overlapping function with EGF; however, a subset of genes was uniquely altered following 6 h of IVM with either treatment. Following 6 h of IVM, both Areg and Ereg were significantly increased by both treatments, whereas Egln3, Nr4a1, Nr4a2, Nr4a3, and Adamts5 were significantly higher following versican treatment compared with EGF. In contrast, Sprr1a and Aqp3 were increased after 6 h of EGF but not versican treatment. To determine whether there were temporal differences, COCs were cultured with EGF or versican for 0–12 h. Versican-induced expression occurred later but remained elevated for longer compared with EGF for Ptgs2, Ereg, and Nr4a3 . The unique expression profiles of Aqp3 and Nr4a3 during IVM were similarly regulated in vivo. These data indicate that versican has EGF-like effects on COC gene expression, but with distinct temporal characteristics.